USER EXPERIENCE IN THE CONTEXT OF DEVELOPING AN APPLICATION FOR CHILDREN WITH AUTISTIC SPECTRUM DISORDER - Serati, Andrew Gabriel Canassi; Gibertoni, Daniela (Revista Interface Tecnológica, 2022)
Developing products aimed at the autistic audience is more challenging than it seems, so it is necessary that the designer has allies so that his work is easier, better guided and more successful. One of these allies may be UX (User Experience), which is an area of science whose goal is to help develop products taking into consideration not only usability, but the whole user experience. The objective of this paper is to evaluate how UX with a focus on accessibility was applied by an internal research group of a public higher education institution in the development of an application aimed at children with autism; considering accessibility as a facet of UX under the UX honeycomb of Morville (2004). The results discussed take into consideration three evaluations by inspection: two of accessibility (accessibility guidelines for users with ASD and GAIA recommendations) and one of usability (Nielsen’s 10 heuristics). With the interpretation and analysis of the results of the evaluations, it becomes possible to define new strategies and reprioritize the application needs in a more agile and effective way.